Characterization 3333 of tomato (Solanum lycopersicum) accessions for resistance to phylotype I and phylotype II strains of the Ralstonia solanacearum species complex under high temperatures. (25th October 2019) - Kunwar, Sanju; Hsu, Yun‐Che; Lu, Shu‐Fen; Wang, Jaw‐Fen; Jones, Jeffrey B.; Hutton, Samuel; Paret, Mathews; Hanson, Peter
Abstract: Bacterial wilt of tomato caused by Ralstonia solanacearum species complex ( RSSC ) causes substantial yield losses in the tropics and subtropics. Disease management options by chemicals are limited, and host resistance is the cheapest and easiest means of control. However, sources of bacterial wilt resistance in tomato are limited. The disease often coincides with higher temperatures in the tropics, and resistance sources that are more heat stable are particularly valuable for breeding of tropically adapted tomato cultivars. The objectives of this study were to identify tomato accessions that demonstrate relatively high bacterial wilt resistance under high temperatures and to identify accessions that may possess QTLs other than Bwr‐6 and Bwr‐12 (two major disease resistance QTLs against bacterial wilt), which could be exploited in future breeding. Sixty‐seven tomato entries reported as bacterial wilt resistant were evaluated in a greenhouse against one strain each of phylotype I (Pss4) and phylotype IIB (Pss1632) of the RSSC (average temperature ≥29°C). Of those, five and 19 were homozygous for Bwr‐6 and Bwr‐12, respectively, and six were homozygous for both QTLs. Bwr‐12 contributed to resistance against phylotype I strain but not against the phylotype II strain. Bwr‐6 contributed to resistance against both phylotype strains. Entries with both QTLs as a group performed relatively better against the phylotype I strain. Entry "94T765‐24‐79", which lacked Bwr‐6 and Bwr‐12, demonstrated relatively high resistance against the phylotype II strain and may carry new QTL/s. As new bacterial wilt resistance QTLs are mapped and markers designed, pyramiding multiple bacterial wilt resistance QTLs into new varieties should be straightforward, thereby increasing the chances of obtaining stable resistance.